NILAI MORAL DALAM FILM FABULOUS UDIN BERDASARKAN PERSPEKTIF SOSIOLOGI KARYA SASTRA - Basid, Abdul; Fitria, Barokatul (BAHASTRA, 2017)
The purpose of this study is to analyze what the shape of morality value, what the causal factor of morality value, and what the impact of of morality value described in Fabulous Udin film. This study is qualitative study. The technique of data collection is watching and noting. The technique of data validation is increasing perseverance, applying triangulation, and discussing with experts. The technique of data analysis is Miles and Huberman model. The result of this study is: 1) the shape of morality value described in Fabulous Udin film is give the one motivation, trying to keep a friendship, having a simple way of life or positive, and demulcenting peopleâs mind load;Â  2) the causal factor of morality value described in Fabulous Udin film is: a) itâs necessary to assure people to act good thing; b) itâs needed to be a sensitive, stiff, and calm person; c) every single action has their own consequence; d) human is a social creature; and 3) the impact of of morality value described in Fabulous Udin film is a) the society well-understand the meaning and purpose of careness and help; b) the society is more care about peopleâs problem; and c)the society is wiser to take a decision.